Which is more effective in thawing frozen rooster sperm: varying temperature or duration? - Nizam, Mustafa Yiğit; Selçuk, Murat; Esin, Burcu (Frontiers in Veterinary Science, 2025)
IntroductionCryopreservation of poultry sperm is crucial for preserving genetic diversity and protecting endangered breeds. Rooster sperm is highly sensitive to cryopreservation due to its high polyunsaturated fatty acid content, making it prone to damage during freezing and thawing. This study evaluated the effects of thawing temperatures and storage conditions on sperm quality, including motility, morphology, and viability.MethodsFrozen rooster semen samples were thawed at 37°C for 30 seconds, 60°C for 5 seconds, or 72°C for 5 seconds and stored at 4°C for up to 48 hours. Sperm quality parameters, including motility, kinematic characteristics, abnormal morphology, and viability, were assessed at 0, 3, 6, 9, 12, 24, and 48 hours using a Computer-Assisted Semen Analyzer (CASA).ResultsPost-thaw motility varied significantly between thawing temperatures at 24 and 48 hours (p < 0.05). Progressive and rapid progressive motility also differed significantly at 24 hours (p < 0.05). Sperm viability showed statistical differences across thawing groups at 24 and 48 hours (p < 0.05), while morphological abnormalities were significant at 12 and 48 hours (p < 0.05). Across all groups, sperm quality parameters varied significantly at each time point (p < 0.05).DiscussionThawing at 37°C and storing at 4°C for up to 24 hours optimizes sperm motility and viability, minimizing cryodamage and ensuring functional preservation. This approach is effective for short-term storage and crucial for sustaining genetic diversity and fertility in poultry breeding programs.